THE EFFECT OF PREGNANCY MASSAGE ON BACK PAIN OF PREGNANT WOMEN IN THE THIRTY TRIMESTER AT KABANJAHE HOSPITAL IN 2023 - handayani; Eva Ratna Dewi; Marlina Simbolon; Adelina Sembiring, (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Pregnancy is a woman's physiological process, which will also involve many physiological and psychological changes. Psychological changes that may occur in a mother during the third trimester of pregnancy include the mother feeling anxiety, depression, disappointment and rejection. These feelings will influence changes in the mother's mood due to hormonal changes that trigger these changes. Physiological changes that often occur in pregnant women in the third trimester are changes in the connective tissue to become softer and looser, which can result in back pain (Astuti, et al: 2017). This research design uses a descriptive research design with a cross-sectional quantitative approach where data for each variable is studied at the same time. Descriptive-quantitative is a research method carried out to describe or illustrate a phenomenon that occurs in society without looking for relationships between variables using statistical procedures or other methods of quantification (measurement). The results of the study show that the results of the Mann Whitney test show that the significant value (p value) is 0.000<0.05, so it can be concluded that Ho is rejected or Ha is accepted, which means that there is a significant difference in the average back pain of third trimester pregnant women between the control group. with the treatment group after intervention with pregnancy massage. Based on the research results and discussion, it can be concluded that there is a significant difference in changes in back pain between the intervention group and the control group.